Who controls the tariffs of a human cell? - Maximilian Billmann (Molecular Systems Biology)
The cell, the functional unit of life, creates well-controlled biochemical environments through partition via membranes and transport of molecules across those membranes via transporters. The human genome encodes for 1500–2000 of such transporters with the largest family, the solute carriers (SLC), comprising around 450 proteins. Despite their crucial physiological role, the large number of disease-linked SLCs, as well as their role as prominent drug targets, as much as one-third of all SLCs lack functional annotation. And even for SLCs with functional annotation, how exactly they act in their complex network to precisely maintain intracellular environments is only anecdotally understood (César-Razquin et al, 2015). To tackle this shortcoming and exploit the immense therapeutic potential, the Resolute consortium built a first virtual landscape of SLC biology by recording and integrating several layers of SLC-centered omics networks. In this issue of Molecular Systems Biology, four studies present the central data generation efforts covering metabolomics and transcriptomics (Wiedmer et al, 2025), proteomics (Frommelt et al, 2025), perturbation omics (pertomics) (Wolf et al, 2025), as well as an integration of these data (Goldmann et al, 2025).